(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2007)
CMC was prepared from agricultural wastes-rice straw and wheat straw. This was then converted via its acidic form of CMC to CoCMC by reaction with Co (II) chloride. A maximum of about 7 % cobalt content in the product, CoCMC, obtained from both the sources was recorded, when 1.0 g of the acid form of CMC was treated with 5.0 g of Co (II) chloride in an overall mixture of 250 ml of water at 90° C for 8 hours. Bangladesh J. Sci. Ind. Res. 41(3-4), 159-166, 2006